Defenisi Gender Menurut Tafsir Dan Kaitannya Dengan Isu Kesetaraan Gender Di Indonesia - Saleh, Musyirah; Sohrah; Rosmini (CV. SINAR HOWUHOWU, 2026)
Indonesia is a country rich in diversity, and the role of religion in life remains a relevant and dynamic topic. Historically, religion has played a significant role in shaping the order of social life. The study of men and women is generally referred to as gender studies. Unlike the term sex, which focuses more on the biological differences between men and women, gender focuses more on the relationship between men and women in terms of their roles and responsibilities. Gender justice and equality are the primary objectives of this study. Gender injustice is the primary issue that becomes the topic of the problem. Gender injustice is the process of marginalization and impoverishment of women. This injustice is caused by several factors, including government policies, traditional beliefs, religious interpretations, customs, and scientific assumptions.